Pelatihan Dan Pendampingan Mahasiswa Diploma III Analis Kesehatan UNUSU Mengola Data Penelitian Berbantuan SPSS - Rusmini Rusmini (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
The use of computers at this time is commonly used by students in the field of research, such as managing research data using the help of SPSS software which can be completed accurately and precisely. However, this SPSS software has a large memory space, so there are a few problems with computers with small RAM, which means that it can be installed but the process is slow when used. The point is that you need patience. But compared to us having to calculate research data one by one, of course, it is not comparable. Therefore, it is important to provide training and assistance on how to install and use and manage research data with SPSS software. Based on this, the PKM University Potential Main Team provided training and assistance to Diploma III Health Analyst students at Nahdlatul Ulama University North Sumatra (UNUSU), because based on observations, the ability of students to manage data using the SPSS application was still low. The training will be held on November 5, 2022 by giving a pretest first. Then materials provide installation and input data on the work page and read the conclusions. The Post Test is given by giving practical questions directly on the computer. After evaluating the results of practice, it can be concluded that the training resulted in the ability of UNUSU Diploma III students to process data significantly better (increase) and students were highly motivated during the training